2019
DOI: 10.1021/acs.jpcc.9b03658
|View full text |Cite
|
Sign up to set email alerts
|

Interface Electrostatics of Solid-State Dye-Sensitized Solar Cells: A Joint Drift-Diffusion and Density Functional Theory Study

Abstract: Dye-sensitized solar cells (DSCs) have gained great attention in recent years due to their low-cost fabrication, flexibility, and high power conversion efficiency. In a DSC, due to interfaces between the dye and the charge-transport materials, the interface electrostatics becomes a key factor determining the overall performance of the cell. Liquid-electrolyte-based DSCs suffer from low stability, electrolyte leakage, and, in some cases, electrode corrosion. Replacing liquid electrolyte with a solid semiconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…On the other hand, this solid-state compound led to poor interfacial contacts, causing interface electrostatics to become one of the limiting factors for reproducible, efficient and stable devices. 277 However, the most important issues regarding Spiro-OMeTAD are related to its sensitivity to both moisture and oxygen and its high production costs, mainly due to its lengthy synthesis protocol, which is low yield with a considerable impact in terms of solvents used for the separation and purification steps. 278,279 Furthermore, it necessitates the addition of additives based on lithium and/or cobalt (a well-known CRM) to boost its conductivity and hole mobility, thus making this system far from the sustainability targets of the DSSC scenario.…”
Section: Reported An Oxovanadium Complex Bearing a Tetradentate Hybeb Ligand (Hybeb = [1-(2-hydroxybenzamido)-2-(2-pyridinecarboxamido)bementioning
confidence: 99%
“…On the other hand, this solid-state compound led to poor interfacial contacts, causing interface electrostatics to become one of the limiting factors for reproducible, efficient and stable devices. 277 However, the most important issues regarding Spiro-OMeTAD are related to its sensitivity to both moisture and oxygen and its high production costs, mainly due to its lengthy synthesis protocol, which is low yield with a considerable impact in terms of solvents used for the separation and purification steps. 278,279 Furthermore, it necessitates the addition of additives based on lithium and/or cobalt (a well-known CRM) to boost its conductivity and hole mobility, thus making this system far from the sustainability targets of the DSSC scenario.…”
Section: Reported An Oxovanadium Complex Bearing a Tetradentate Hybeb Ligand (Hybeb = [1-(2-hydroxybenzamido)-2-(2-pyridinecarboxamido)bementioning
confidence: 99%
“…They observed that due to the presence of carboxylic groups in the molecule, crocetin shows increased binding affinity to the porous TiO 2 surface. Increased TiO 2 dye binding results in increased pore-filling and efficient electron injection from crocetin molecules to TiO 2 91,92 . Short-circuit photocurrents of 2.84 mA and 0.45 mA were reported for the cells based on crocetin and crocin, respectively.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…They obtained poor DSC efficiency (0.076%), which could be due to poor binding of βcarotene to the TiO 2 surface as β -carotene does not have carboxylic or hydroxyl groups. Poor pore filling and poor binding of dye molecules to the TiO 2 surface results in poor electron injection from the β -carotene dye to TiO 2 71,91,92 . In another study, Eka et al 70 extracted carotenoids from Citrus medica var Lemon and Musa aromatica and used them as photosensitizers for DSCs with TiO 2 Nanoparticle.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…A finite-element drift-diffusion model is implemented in TiberCAD [46,47]. The model can perform 3-dimensional simulations, and has already been used to simulate organic solar cells [48], organic field-effect transistors [49], PSCs [14,50] and dye-sensitized solar cells [51]. Within the model, Poisson and drift-diffusion equations are solved simultaneously for electrons, holes, and trapping centers, considering the light absorption and the charge carrier generation-recombination processes.…”
Section: Simulation Modelmentioning
confidence: 99%